Вплив кількох обставин, що пом’якшують покарання, та неповнолітнього віку особи на істотне зниження ступеня тяжкості вчиненого злочину - Чупринський, Б.; Chuprynskii, B. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджуються особа неповнолітнього, обставини, що пом’якшують покарання неповнолітнім, ступінь тяжкості вчиненого злочину вплив обставин, що пом’якшують покарання та особи неповнолітнього на істотне зниження ступеня тяжкості вчиненого злочину, передбачених загальною частиною Кримінального права України. Розглядається гуманізація кримінального законодавства щодо призначення покарання неповнолітнім, забезпечуючи охорону основних прав і свобод неповнолітнього злочинця. Аналізується вікові соціально-психологічні властивості неповнолітнього і їх вплив на кримінальну поведінку неповнолітньої особи та обов’язковість судами урахування пом’якшуючих обставин та індивідуальний підхід при визначенні ступеня тяжкості вчиненого злочину неповнолітнім. The article analyzes the age and sociopsychological characteristics of juvenile and theirinfluence on the behavior of the minors, laying emphasis on the mandatory incorporation by court of the mitigating circumstances and individual approach in determining the gravity of the offenses committed by a minor. When sentencing minors the court ought to take into account the issues of living conditions, education and other aspects: family circumstances; the material conditions of life and upbringing of a minor; attendance of school or other educational institutions; the level of academic success and behavior, relationships with teachers and educators; relations with other minors, the level of physical and intellectual development, the ability to comprehend the facts and the social consequences of the committed offences; the previous behavior of the minor, the minor’s behavior after committing the crime, in particular his attitude tothe victim, the behavior during the pre-trial investigation and in court proceedings; the presence of moral responsibility to take care of other family members and his attitude towards this obligation; attitude of minorto the offenses committed by others and to the designated punishment, its legal effects.
Impact of Certain Factors, that Mitigate Punishment, and the Underage of a Person on the Severity Degree of the Crime Committed
Keywords: обставини, що пом’якшують покарання; особа неповнолітнього; ступінь тяжкості вчиненого злочину; гуманізація кримінального законодавства; призначення покарання неповнолітнім; the circumstances that mitigate punishment; minors; the severity of the crime; humanization of criminal legislation; sentencing